Malignancy in Thyroid Nodules with Bethesda III Category on Repeat Fine Needle Aspiration Biopsy - Ng, Jennifer Lourdes; Escueta, Luz Margaret; Dampil, Oliver Allan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objectives. This study aimed to evaluate the risk of malignancy for nodules repeatedly classified as Bethesda category III on fine needle aspiration biopsy (FNAB). Methodology. A chart review on a series of 59 patients seen with thyroid nodules who underwent both initial and repeat FNAB at the Diabetes, Thyroid and Endocrine Center of St. Luke’s Medical Center, Quezon City was conducted. The Thyroid Registry was utilized to collect each patient’s demographic and clinical characteristics, ultrasonographic features of thyroid nodules along with the cytopathologic and histopathologic results. The subclassification of atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) were retrieved from the cytopathology reports using the institution’s electronic Healthcare-Results Management System. Results. A total of 59 adult patients with thyroid nodules were included. Nodules which were initially AUS/FLUS turned out to be malignant on repeat FNAB in 38 patients with a prevalence of 64.41% (95% CI: 50.87-76.45%). There was no significant difference with regards to clinical, ultrasonographic and cytopathologic features of malignancy between benign and malignant nodules. Conclusion. Findings of this study support surgical intervention as a reasonable option after a repeat Bethesda III classification on FNAB. However, the small sample size warrants confirmation in future studies with a representative sample of patients.